Canonical toric Fano threefolds - Kasprzyk, Alexander M. (University of Toronto Press, 2010)
An inductive approach to classifying toric Fano varieties is given. As an application of this technique, we present a classification of the toric Fano threefolds with at worst canonical singularities. Up to isomorphism, there are 674,688 such varieties.